PERANCANGAN PENGENDALIAN SUHU DAN SALINITAS AIR PADA AQUARIUM IKAN BOTANA BIRU - Abdul Haris Kadafi; Sujono Sujono (MAESTRO, 2020)
In this final project has been designed a device to control temperature and salinity of sea water in the aquarium blue botana (Acanthurus leucosternon). This designed system consists of a temperature sensor, salinity sensor, microcontroller, chiller, heater, LCD, DC pump, and Aquarium. The controller in the system consists of 2 types, namely the on / off controller that is used to turn on the chiller when the sensor signals to the controller algorithm that the temperature is above 28 ̊C and will be off at 26 ̊C, the two on / off controllers are used to turn on the heater when the temperature is below 25 ̊ C until the temperature reaches 26 ̊ C, the heater will turn off, and the third fuzzy logic controller to start the saltwater pump when salinity is below 29 ppt and start the fresh water pump when the salinity is above 30 ppt. In the fuzzy controller the fuzzy controller input is error and delta error while the output is pulse width modulation. Each input and output variable is classified in 5 membership functions. The defuzzification method used is the centroid method. The results obtained are the control system response has 15% overshoot and 0.5 ppt steady state error, with range of 26-32 ppt with a setpoint of 29 ppt.